Effectiveness of Public Private Partnership model of dairy farming in Haryana - Raj, Khusboo; Ponnusamy, K; Yadav, Raja; CN, Kishore; Begum, Mehrunnissa (Indian Journal of Dairy Science, 2020)
A study was undertaken to assess effectiveness of Public Private Partnership (PPP) model in dairy farming in three districts representing three different agro climatic zones of Haryana namely Kaithal, Hissar and Mahendragarh during 2017-18. Total 225 respondents were selected out of which 45 were private functionaries,30 public functionaries and 150 were farmers. Interview schedule was used to elicit the response from them. Ex-post facto research design was used for study. An effectiveness index was developed in order to assess the effectiveness of PPP model in dairy farming. Study revealed that Effectiveness index score of farmers about utility and access to technical services was highest (0.62) which shows that farmers are able to access the technical services in dairying effectively through PPP approach although the main role of Gopal (private extension functionary) was focused on delivering AI services. Farmer’s effectiveness index score on profit maximization was 0.60 which show that farmers considered PPP to be effective in realizing maximum profit. Effectiveness index score of transparency was very low (0.48) which indicate that farmers expectation on transparency in service delivery was still very high. The findings suggest the further improvement of effectiveness of PPP model through focus on capacity building, better transport facility for Gopal, effective monitoring by public extension functionaries, periodic coordination meeting and village level veterinary camp.A study was undertaken to assess effectiveness of Public Private Partnership (PPP) model in dairy farming in three districts representing three different agro climatic zones of Haryana namely Kaithal, Hissar and Mahendragarh during 2017-18. Total 225 respondents were selected out of which 45 were private functionaries,30 public functionaries and 150 were farmers. Interview schedule was used to elicit the response from them. Ex-post facto research design was used for study. An effectiveness index was developed in order to assess the effectiveness of PPP model in dairy farming. Study revealed that Effectiveness index score of farmers about utility and access to technical services was highest (0.62) which shows that farmers are able to access the technical services in dairying effectively through PPP approach although the main role of Gopal (private extension functionary) was focused on delivering AI services. Farmer’s effectiveness index score on profit maximization was 0.60 which show that farmers considered PPP to be effective in realizing maximum profit. Effectiveness index score of transparency was very low (0.48) which indicate that farmers expectation on transparency in service delivery was still very high. The findings suggest the further improvement of effectiveness of PPP model through focus on capacity building, better transport facility for Gopal, effective monitoring by public extension functionaries, periodic coordination meeting and village level veterinary camp.A study was undertaken to assess effectiveness of Public Private Partnership (PPP) model in dairy farming in three districts representing three different agro climatic zones of Haryana namely Kaithal, Hissar and Mahendragarh during 2017-18. Total 225 respondents were selected out of which 45 were private functionaries,30 public functionaries and 150 were farmers. Interview schedule was used to elicit the response from them. Ex-post facto research design was used for study. An effectiveness index was developed in order to assess the effectiveness of PPP model in dairy farming. Study revealed that Effectiveness index score of farmers about utility and access to technical services was highest (0.62) which shows that farmers are able to access the technical services in dairying effectively through PPP approach although the main role of Gopal (private extension functionary) was focused on delivering AI services. Farmer’s effectiveness index score on profit maximization was 0.60 which show that farmers considered PPP to be effective in realizing maximum profit. Effectiveness index score of transparency was very low (0.48) which indicate that farmers expectation on transparency in service delivery was still very high. The findings suggest the further improvement of effectiveness of PPP model through focus on capacity building, better transport facility for Gopal, effective monitoring by public extension functionaries, periodic coordination meeting and village level veterinary camp.A study was undertaken to assess effectiveness of Public Private Partnership (PPP) model in dairy farming in three districts representing three different agro climatic zones of Haryana namely Kaithal, Hissar and Mahendragarh during 2017-18. Total 225 respondents were selected out of which 45 were private functionaries,30 public functionaries and 150 were farmers. Interview schedule was used to elicit the response from them. Ex-post facto research design was used for study. An effectiveness index was developed in order to assess the effectiveness of PPP model in dairy farming. Study revealed that Effectiveness index score of farmers about utility and access to technical services was highest (0.62) which shows that farmers are able to access the technical services in dairying effectively through PPP approach although the main role of Gopal (private extension functionary) was focused on delivering AI services. Farmer’s effectiveness index score on profit maximization was 0.60 which show that farmers considered PPP to be effective in realizing maximum profit. Effectiveness index score of transparency was very low (0.48) which indicate that farmers expectation on transparency in service delivery was still very high. The findings suggest the further improvement of effectiveness of PPP model through focus on capacity building, better transport facility for Gopal, effective monitoring by public extension functionaries, periodic coordination meeting and village level veterinary camp.A study was undertaken to assess effectiveness of Public Private Partnership (PPP) model in dairy farming in three districts representing three different agro climatic zones of Haryana namely Kaithal, Hissar and Mahendragarh during 2017-18. Total 225 respondents were selected out of which 45 were private functionaries,30 public functionaries and 150 were farmers. Interview schedule was used to elicit the response from them. Ex-post facto research design was used for study. An effectiveness index was developed in order to assess the effectiveness of PPP model in dairy farming. Study revealed that Effectiveness index score of farmers about utility and access to technical services was highest (0.62) which shows that farmers are able to access the technical services in dairying effectively through PPP approach although the main role of Gopal (private extension functionary) was focused on delivering AI services. Farmer’s effectiveness index score on profit maximization was 0.60 which show that farmers considered PPP to be effective in realizing maximum profit. Effectiveness index score of transparency was very low (0.48) which indicate that farmers expectation on transparency in service delivery was still very high. The findings suggest the further improvement of effectiveness of PPP model through focus on capacity building, better transport facility for Gopal, effective monitoring by public extension functionaries, periodic coordination meeting and village level veterinary camp.A study was undertaken to assess effectiveness of Public Private Partnership (PPP) model in dairy farming in three districts representing three different agro climatic zones of Haryana namely Kaithal, Hissar and Mahendragarh during 2017-18. Total 225 respondents were selected out of which 45 were private functionaries,30 public functionaries and 150 were farmers. Interview schedule was used to elicit the response from them. Ex-post facto research design was used for study. An effectiveness index was developed in order to assess the effectiveness of PPP model in dairy farming. Study revealed that Effectiveness index score of farmers about utility and access to technical services was highest (0.62) which shows that farmers are able to access the technical services in dairying effectively through PPP approach although the main role of Gopal (private extension functionary) was focused on delivering AI services. Farmer’s effectiveness index score on profit maximization was 0.60 which show that farmers considered PPP to be effective in realizing maximum profit. Effectiveness index score of transparency was very low (0.48) which indicate that farmers expectation on transparency in service delivery was still very high. The findings suggest the further improvement of effectiveness of PPP model through focus on capacity building, better transport facility for Gopal, effective monitoring by public extension functionaries, periodic coordination meeting and village level veterinary camp.